In Vitro and In Vivo Antidermatophyte Activities of NND-502, a Novel Optically Active Imidazole Antimycotic Agent - Niwano, Yoshimi (American Society for Microbiology, 1998)
In vitro and in vivo antidermatophyte activities of NND-502, a new imidazole antimycotic agent, were compared with those of two existing antifungal agents, lanoconazole and terbinafine. NND-502 exhibited strong in vitro antifungal activity against Trichophyton spp.; its MIC was 1 to 4 times lower than that of lanoconazole or terbinafine. In an in vivo study with a guinea pig model of tinea pedis, 7-day topical treatment with a 0.5% solution of NND-502 (dissolved in polyethylene glycol 400) was more effective than that with a 0.5% solution of either lanoconazole or terbinafine for eradicating fungi from the infected feet. When the duration of treatment was shortened to 3 days, a topical 1% solution of NND-502 achieved a complete mycological cure, while topical 1% solutions of lanoconazole and terbinafine did not.